2020
DOI: 10.1186/s12886-020-1328-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of tear film and the morphological changes of meibomian glands in young Asian soft contact lens wearers and non-wearers

Abstract: Background The aim of this study was to explore the differences in terms of tear film and meibomian glands (MGs) between young Asian soft contact lens (CL) wearers and non-wearers. Methods A prospective, cross-sectional observational study was conducted using 148 subjects (63 non-wearers, and 85 soft CL wearers who had been wearing CLs for more than 1 year) recruited from a clinic in Tianjin, China. All subjects first responded to an Ocular Surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 49 publications
0
33
2
Order By: Relevance
“…There was no significant difference in average Meibomian gland dropout between rigid corneal lens wearers and hydrogel lens wearers [63]. Another, more recent study which also evaluated the effect of contact lens wear on Meibomian glands in an Asian population supports these findings in that contact lens wear negatively affects Meibomian glands and, furthermore, the structural changes worsen with years of wear [65]. Other researchers have also reported apparent changes to Meibomian glands related to contact lens wear [66,67].…”
Section: Meibomian Gland Changesmentioning
confidence: 83%
See 1 more Smart Citation
“…There was no significant difference in average Meibomian gland dropout between rigid corneal lens wearers and hydrogel lens wearers [63]. Another, more recent study which also evaluated the effect of contact lens wear on Meibomian glands in an Asian population supports these findings in that contact lens wear negatively affects Meibomian glands and, furthermore, the structural changes worsen with years of wear [65]. Other researchers have also reported apparent changes to Meibomian glands related to contact lens wear [66,67].…”
Section: Meibomian Gland Changesmentioning
confidence: 83%
“…In addition, there was no difference in pre-lens tear break-up time between symptomatic or asymptomatic groups [82]. Many other studies have shown that subjective symptoms are related to contact lens wear [57,61,65,66,72] but on the other hand, there are also some that did not observe this relation [59,60,71,83,84]. The influence of overnight orthokeratology (ortho-k) on Meibomian glands has also received some attention in the literature.…”
Section: Meibomian Gland Changesmentioning
confidence: 99%
“…CLIDE may also be associated with increased meibomian gland drop out [316,317], plugged gland orifices [318] or altered meibomian gland function (MGD) [319] (see Section 9). It may contribute to changes in lipid layer thickness and integrity [320], tear instability and decreased lens wettability due to a buildup of lipid deposits on the contact lens surface [321].…”
Section: Pathophysiologymentioning
confidence: 99%
“…-Meibomian gland expression -Meibomian gland imaging (infrared Meibography, Spectral domain, OCT, and confocal microscopy Increased meibomian gland morphological changes and drop-out [316,317,319].…”
Section: B Meibomian Glands Assessmentmentioning
confidence: 99%
“…This disease was defined by the 2011 International Workshop on MGD as "a chronic, diffuse abnormality of the Meibomian glands, commonly characterized by terminal duct obstruction and/or qualitative/quantitative changes in the glandular secretion" [15]. Some studies concluded that soft and rigid contact lens wear may potentiate meibomian gland drop-out, alter gland morphology such as length and width, alter meibum expressibility and quality, and induce dry eye symptoms, ultimately classified as MGD [22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%